Structuring the debate about research ethics in the psychology and law field: An international perspective - Allan, Alfred (2020)
Forensic psychologists’ role is well established, and they are rightly well regulated because their decisions and behaviour can have a significant impact on people’s rights and interests. Their ethical integrity, however, partly hinges on the psycholegal research products (data, methods and instruments) that they and others use. The ethical regulation of researchers who produce products and their research processes is, however, fragmented, limited and narrow and largely focuses on domestic research. Relatively few scholars have examined the regulation of psycholegal research or commented on the ethical implications of recent court decisions. The purpose of this paper is to start a debate about the ethical regulation of researchers in the psycholegal field and consider methods of improving it to maintain society’s trust in the field